2016
DOI: 10.1038/srep36027
|View full text |Cite
|
Sign up to set email alerts
|

Available sustainable alternatives replace endangered animal horn based on their proteomic analysis and bio-effect evaluation

Abstract: The use of endangered animal products in traditional Chinese medicine (TCM) and other ethno-medicines is culturally widespread across many regions of Asia. In the present study, traditional efficacies of seven types of animal horn including antipyretic, sedative and procoagulant activities were evaluated. Shotgun proteomic analysis was performed on material from horns following separation into soluble and insoluble fractions. Over 200 proteins were identified in each sample using nano LC-MS/MS, and these were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Another study that evaluated the effect of animal horns on yeast‐induced fever in rats found that one hour after the oral administration, Saiga horn extract significantly reduced the levels of TNF‐α and PGE2. Two hours after the oral administration, the levels of TNF‐α and IL‐6 were significantly reduced while the level of PGE2 returned to a level similar to the fever group . Again, this indicates that the fever‐lowering effect may be attributed to BHB.…”
Section: Discussionmentioning
confidence: 74%
“…Another study that evaluated the effect of animal horns on yeast‐induced fever in rats found that one hour after the oral administration, Saiga horn extract significantly reduced the levels of TNF‐α and PGE2. Two hours after the oral administration, the levels of TNF‐α and IL‐6 were significantly reduced while the level of PGE2 returned to a level similar to the fever group . Again, this indicates that the fever‐lowering effect may be attributed to BHB.…”
Section: Discussionmentioning
confidence: 74%
“…Modern clinical Chinese research found that horns of water buffalo, domestic cattle, yaks and goats could be substituted for rhino horn, as they have similar chemical compositions and medical actions (Nowell, 2012, Liu et al, 2016. Hence, Liu et al (2016) found rhino horn was not "not especially unique or indispensable" (p. 9). Horns, hooves and nails of different species are not the same chemically, as they all vary in the make up of their keratin protein composition (Nowell, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2). The pharmacopoeia of The Divine Peasants Herbal (Shennong Bencao Jing,Han dynasty, listed rhino horn as a detoxifier and nonspecific health tonic (Liu et. al, 2016;Nowell, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of using horns from non endangered, abundant, and domesticated species as replacement for RH and SAH is being investigated. RH has been replaced by WBH in clinical applications , and GH is also currently used in the clinic and in the pharmaceutical industry as a substitute for SAH .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, over 200 proteins were identified from animal horns, including a large number of keratins (KRTs). Nano‐LC‐MS/MS was used for protein/peptide identification and characterization of animal horns, and some meaningful results were obtained . The proteomic composition of GH is similar to that of SAH, and WBH is similar to RH.…”
Section: Introductionmentioning
confidence: 99%